Tivantinib, a New Option for Second-line Treatment of Advanced Hepatocellular Carcinoma? The Experience of Italian Centers. Issue 2 (March 2015) - Rimassa, Lorenza; Santoro, Armando; Daniele, Bruno; Germano, Domenico; Gasbarrini, Antonio; Salvagni, Stefania; Masi, Gianluca; Abbadessa, Giovanni; Lamar, Maria; Goldberg, Terri; Porta, Camillo
In the last decades the management of hepatocellular carcinoma (HCC) has undergone significant changes following the introduction of novel therapies such as sorafenib, which have improved patient survival. Nevertheless, HCC is still the third most common cause of cancer-related death worldwide. The evidence-based therapy for advanced HCC that is unsuitable for locoregional treatment is limited to sorafenib, with no second-line option available. This article focuses on the development of the MET inhibitor tivantinib in HCC as a promising treatment option for patients who failed sorafenib. A randomized, placebo-controlled phase II study showed activity of tivantinib in patients with high MET expression. Based on these results, the METIV-HCC phase III study in second-line treatment for MET-high patients was initiated to demonstrate the survival advantage of tivantinib compared to placebo.